Legal Protection for Consumers in Transactions Through International E-Commerce Platforms Between Indonesia and China - Malikal Bulqis; Mushafi Miftah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
In addition to bringing advantages like easy access to foreign goods at competitive costs and altering global consumption patterns, the growth of cross-border e-commerce has also brought up complicated legal issues, especially with regard to consumer protection. In Indonesia, consumer protection regulations still focus more on domestic transactions, making them less effective for international transactions China, on the other hand, has a more comprehensive regulatory framework for controlling foreign e-commerce, however there are still issues with transparency and oversight in its execution. With a focus on popular platforms like Tokopedia, Bukalapak, AliExpress, and JD.com, this study contrasts the legislative frameworks for consumer protection in cross-border e-commerce transactions between Indonesia and China. The study's findings demonstrate that although Indonesia continues to struggle with interagency coordination and regulation execution, China leads the world in centralized oversight and consumer education programs. In order to establish a secure, equitable, and long-lasting e-commerce ecosystem, this study suggests that Indonesia take a more integrated strategy, bolster digital supervision, and enhance public education.